The Influence of Entrepreneurship Education and Self-Efficacy on Entrepreneurial Spirit through Student Involvement in the Teaching Factory at SMK N 1 Batang - Widhyaningrum, Affida (Jurnal Profesi Keguruan, 2025)
Vocational High Schools (SMK) are educational institutions where the learning process applies vocational knowledge or field practice, not merely theoretical knowledge in schools. The aim of vocational high schools is not only to prepare students to enter the workforce but also to develop an entrepreneurial spirit, enabling them to create job opportunities. To foster an entrepreneurial spirit from an early age, entrepreneurship education in schools is necessary. Additionally, positive self-efficacy is a factor that can nurture the entrepreneurial spirit. This study aims to determine the impact of entrepreneurship learning and self-efficacy on the entrepreneurial spirit through student involvement in the Teaching Factory. The approach used in this research is a quantitative approach with a causality design. The population of this study consists of 143 students from the Visual Communication Design program at SMK Negeri 1 Batang. The data collection technique used was a questionnaire. Data analysis techniques included descriptive statistical analysis, classical assumption tests, path analysis, and hypothesis testing. The results of this study are: There is a significant impact of entrepreneurship learning on the entrepreneurial spirit, there is no significant impact of self-efficacy on the entrepreneurial spirit, there is a significant impact of student involvement in the Teaching Factory on the entrepreneurial spirit, there is a significant impact of the perception of entrepreneurship learning through student involvement in the Teaching Factory on the entrepreneurial spirit, and there is a significant impact of self-efficacy through student involvement in the Teaching Factory on the entrepreneurial spirit. Student involvement in the Teaching Factory is able to fully mediate entrepreneurship learning. Similarly, student involvement in the Teaching Factory is able to mediate self-efficacy on the entrepreneurial spirit. Good entrepreneurship learning and a sufficient level of self-efficacy are capable of influencing the development of students' entrepreneurial spirit.